2008
DOI: 10.1101/gr.078303.108
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and length of simple repeats in vertebrate genomes are determined by their structural properties

Abstract: Microsatellites are abundant in vertebrate genomes, but their sequence representation and length distributions vary greatly within each family of repeats (e.g., tetranucleotides). Biophysical studies of 82 synthetic single-stranded oligonucleotides comprising all tetra-and trinucleotide repeats revealed an inverse correlation between the stability of folded-back hairpin and quadruplex structures and the sequence representation for repeats Ն30 bp in length in nine vertebrate genomes. Alternatively, the predicte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
105
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 54 publications
10
105
1
2
Order By: Relevance
“…Moreover, our current data provide a molecular mechanism to explain the hairpin reversal-mediated suppression of TNR instability in human cells. Importantly, in our experiment we used unmodified DNA rather than modified RNA, which has been found to minimize the introduction of mutations at the targeted loci (56). It was reported that unmodified singlestranded oligonucleotides could incorporate into the nascent strand, minimizing checkpoint activation and DNA damage in human cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our current data provide a molecular mechanism to explain the hairpin reversal-mediated suppression of TNR instability in human cells. Importantly, in our experiment we used unmodified DNA rather than modified RNA, which has been found to minimize the introduction of mutations at the targeted loci (56). It was reported that unmodified singlestranded oligonucleotides could incorporate into the nascent strand, minimizing checkpoint activation and DNA damage in human cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, different lengths of coding trinucleotide and hexanucleotide repeats, which do not alter the reading frame, have been correlated with skeletal morphology in dogs (8), mating behavior in prairie voles (9), and circadian rhythms in a number of species (2). The mutability of repeats, combined with their incremental effects on protein levels and activity, suggests they could be effective agents for evolutionary plasticity, a hypothesis reinforced by the overrepresentation of trinucleotide repeats (TNRs) in coding regions and their enrichment in genes for transcription factors and other regulatory proteins (10,11).…”
mentioning
confidence: 99%
“…Folded DNA Structures and Abundance of Simple Repeats in Chromosomes-During the course of our genomic investigations, A. Bacolla et al (61) recognized that the abundance of certain repeating tetranucleotide sequences was extremely variable in the human genome, ranging from no copies at all to ϳ15,000/genome. Upon examination of the sequence features of the repeating tetranucleotides that were absent, he predicted that the sequences that were most likely to fold into hairpin loop arrangements were the sequences that were absent.…”
Section: Molecular Mechanisms Of Genetic Instabilities In Hered-mentioning
confidence: 99%